Cigarette Smoking, Mental Health, and Other Substance Use among Court-Involved Youth. (17th February 2020) - Harrison, Anna; Ramo, Danielle; Hall, Sharon M.; Estrada-Gonzalez, Vanessa; Tolou-Shams, Marina
Abstract: Background: Justice-involved youth are at risk to become cigarette smokers as they age, leading to a variety of poor health outcomes. However, little is known about cigarette use among justice-involved youth, especially youth supervised in the community where there is ample opportunity to smoke. Objective: This study investigates the prevalence of cigarette smoking and the associations between cigarette smoking, emotional and behavioral functioning, and other substance use among a sample of first-time offending court-involved, non-incarcerated (FTO-CINI) youth. Methods: Youth were recruited from a family court in the Northeast ( N = 423). Substance use was self-reported using the Adolescent Risk Behavior Assessment (ARBA). Emotional and behavioral functioning was measured using the Behavior Assessment Schedule for Children-Second Edition (BASC-2), the Affect Dysregulation Scale (ADS), National Stressful Events Survey PTSD Short Scale (NSESSS), and the National Survey of Self-Reported Delinquency (NYS-SRD). Results: About 9.9% of FTO-CINI youth had smoked cigarettes in the past 30 days. Compared with FTO-CINI youth who had not smoked recently, recent smokers endorsed more emotional and behavioral symptoms, such as school problems ( p < .001), internalizing problems ( p = .012), inattention/hyperactivity ( p = .020), affect dysregulation ( p = .044), PTSD symptoms ( p = .006), and delinquent behavior ( p < .001). Recent smokers were also more likely to use alcohol (OR = 5.61, p < .001), marijuana (OR = 11.27, p < .001), and other drugs (OR = 5.00, p < .001). Conclusions: Recent smoking was higher among FTO-CINI youth than youth in the general population. Findings underscore the need to incorporate nicotine into existing substance use prevention interventions for this population, who are at high risk to initiate cigarette use as they age.